Prognosis and characteristics of Corynebacterium exit site infection: a single-center retrospective study - Kazuya Sugita; Naoki Washida; Jyunji Takahashi; Masashi Tsunematsu; Kozi Hosoya; Jun Ito; Yutaka Suzuki; Kiyotaka Uchiyama (Renal Replacement Therapy, 2024)
Abstract Background Corynebacterium is a rare but important cause of peritoneal dialysis (PD)-associated infection. A previous study reported that continued antibiotic use at the exit site is associated with increased Corynebacterium exit site infection (ESI), although the latest International Society of Peritoneal Dialysis guideline recommends its use. This study aims to verify the prognosis of Corynebacterium-associated PD-related infections, focusing on ESI. Methods We conducted a single-center, retrospective study about ESI, tunnel infection (TI), and PD-associated peritonitis due to Corynebacterium between April 2018 and January 2023. We primarily examined the prognosis and characteristics of Corynebacterium ESI. Results In this study, we included 125 patients with PD (mean age at PD onset: 69.4 ± 13.7 years, 71.2% male, 48% diabetic, mean estimated glomerular filtration rate at the introduction of PD 7.4 ± 2.6 ml/min/1.73 m2, total follow-up 179.6 patient dialysis year). Between April 2018 and January 2023, 191 cases of ESI, 62 cases of Corynebacterium ESI in 24 patients, 10 cases of TI, and 32 cases of PD-associated peritonitis were detected. In total, 16 of 24 patients with Corynebacterium-associated ESI tested positive for Corynebacterium multiple times in cultures against the exit site, with a maximum of eight times. The estimated glomerular filtration rate during PD introduction was relatively lower in patients with Corynebacterium-associated ESI than in patients without ESI (6.4 versus 7.9 mL/min/1.73 m2, respectively; P = 0.052). Although three of the Corynebacterium ESI cases progressed to TI, there were no cases that progressed directly to PD-associated peritonitis. Conclusions Corynebacterium-associated ESI progresses to TI with a certain probability; however, it is thought that it rarely progresses to PD-associated peritonitis directly.